A Composite Perforated Partitioned Sandwich Panel With Corrugation for Underwater Low-Frequency Sound Absorption - Wang, Junyi; Hu, Jiaming; Chen, Yun (Frontiers in Mechanical Engineering, 2021)
Underwater acoustic wave absorption and control play an important role in underwater applications. Various types of underwater acoustic metamaterials have been proposed in recent years with the vigorous development of acoustic metamaterials. Compared with airborne sound, underwater sound waves have a longer wavelength and much smaller propagation loss, making them more difficult to control. In addition, given that the acoustic impedance of water is much greater than that of air, numerous conventional materials and structures are not suited to underwater use. In this paper, we propose a composite structure based on an excellent broadband low-frequency sound absorber of air using aluminum mixed with rubber. Our composite structure possesses broadband low-frequency (<1,000 Hz) sound absorption underwater, omnidirectional high sound absorption coefficient under the oblique incidence (0– 75°), and pressure resistance. It has promising applications for underwater acoustic wave control and contributes to the design of underwater acoustic metamaterials.